(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the investigation of the spiritual growth problems of the Evangelical ChristianBaptists Confession communities in the southern part of Ukraine in the 20ties of the 20th century. On the basis of archive sources, the author considers the main obstacles to the spiritual growth of the communities and the ways to overcome them